Communication—Enhancement of Boron Back-Surface-Field and Suppression of Auger Recombination to Improve Ultralow-Reflectance Si Solar Cells. (1st May 2020) - Kunieda, Shogo; Imamura, Kentaro; Kobayashi, Hikaru
Abstract : A high conversion efficiency of 20.2% is achieved for simple structured-Si solar cells without a conventional anti-reflection layer. The ultralow-reflectance less than ∼3% is achieved by formation of a nanocrystalline Si (nc-Si) layer using the surface structure chemical transfer (SSCT) method which takes only 15 s. The nc-Si layer is passivated by phosphosilicate glass, while the rear Si surface is passivated by boron back-surface-field (B-BSF). By optimizing diffusion conditions, a high short-circuit current density of 41.8 mAcm −2 and improvement of an open-circuit voltage are achieved owing to enhancement of B-BSF and suppression of Auger recombination in the phosphorus-doped nc-Si layer.